Perbandingan Perlindungan Minyak Jintan Hitam, Minyak Argan dan Minyak Zaitun terhadap Enzim Hati Tikus Akibat Diet Tinggi Lemak - Liska Alfaaizin; Aryadi Arsyad; Yulia Yusrini Djabir (Jurusan Farmasi Universitas Negeri Gorontalo, 2023)
High-fat diet has become one of the risk factors of liver dysfunction due to accumulation of fat in the liver cells. This disorder might be triggered by increased reactive oxygen species (ROS) activity with high-fat consumption. This study aimed to compare protective effect of natural antioxidants black cumin oil, argan oil and olive oil on liver function in wistar rats fed with high-fat diet. Male wistar rats (n = 24) were divided into four treatment groups. Group 1 (negative control) was not given any oil treatment (0,5 ml/g bw), group 2 was given black cumin oil (0,4 ml/g bw), group 3 was given argan oil (0,5 ml/g bw) and group 4 was given olive oil (0,5 ml/g bw). All rats were fed a high-fat diet of 10 gr/day for 2 months. The analysis of liver function tests was performed before and after treatment. With high-fat diet, the negative controls had SGOT of 93.05 ± 47.91 UI/I and SGPT of 43.10 ± 14.64 UI/l. Administration of black cumin oil markedly reduced SGOT (62.05 ± 30.67 UI/l) and SGPT levels (28.81 ± 10.60 UI/l) (P0.05). Argan oil can not reduce SGOT levels (97.92 ± 35.07 UI/l) but can reduce SGPT levels (51.67 ± 15.84 UI/l). Olive oil can not reduce SGOT levels (67.38 ± 29.31 UI/l) but can reduce SGPT levels (50.19 ± 9.70 UI/l). It was concluded that administration of black cumin is more effective to reduce SGOT and SGPT levels in rats with high-fat diet compared to argan oil and olive oil treatments.